Desain Sistem Informasi Laporan Keuangan Berbasis Microsoft Excel Pada Usaha Bengkel Las Sumber Berkat Manado - Mustopa, Opa; Tampenawas, Maykel A.; Rombot , Raymond F.; Rompas, Jufry (Cattleya Darmaya Fortuna, 2025)
Computer-based financial reporting information systems have now become very important for the information needs of a company. This is because the presence of computer-based information systems can facilitate work with quick, accurate, and cost-effective processes. This is very different from manual processes, where errors often occur, accuracy is lacking, and the presentation of financial reports always experiences delays, which is detrimental to the company's information needs. The problem faced in the field is that many SMEs have not yet adopted computer-based information systems due to limitations in resources and knowledge, both in accounting and computer skills, as is the case with the Sumber Berkat Manado SME, which highlights the urgency of this research. Therefore, the researcher conducts a study aimed at designing financial reports for SMEs based on Microsoft Excel for the Sumber Berkat Welding Workshop in Manado. The research method used is the Interactive Model of Analysis, with stages of data collection, data reduction, data display, and conclusion drawing and verification. The results show that the design of a financial reporting information system using Microsoft Excel can facilitate MSME actors in creating financial reports, allowing them to accurately assess the profits and losses incurred during a specific period from their business results, and enabling them to monitor their business development at any time. Keywords: Design; Information System; Financial Reports; MSMEs; Microsoft Excel